Evaluation of Pulse Oximetry Screening Rates Among the Midwife‐Attended Out‐of‐Hospital Birth Community in Michigan. (14th March 2019) - Withrow, Evan; Fussman, Chris; Thompson, Kristen; Kleyn, Mary
Abstract : Introduction: In Michigan, pulse oximetry screening rates for critical congenital heart defects (CCHDs) are assessed for birthing hospitals but have not been assessed for the midwife‐attended births that occur in the out‐of‐hospital birth community. This analysis was conducted to determine pulse oximetry screening rates among the midwife‐attended out‐of‐hospital birth community in Michigan overall, and among midwives provided with loaned pulse oximeters from the Michigan Department of Health and Human Services (MDHHS). Methods: Records for midwife‐attended out‐of‐hospital births between April 1, 2014, and December 31, 2016, were linked via probabilistic matching with newborn screening records. Pulse oximetry screening rates were calculated for the midwife‐attended out‐of‐hospital birth population overall, by midwife, and stratified by receipt of loaned pulse oximeters from MDHHS. Births from midwives who attended 5 or more nonhospital births during the study period were included in this analysis. Results: Of the 3410 midwife‐attended out‐of‐hospital births, 20.8% (n = 710) reported as having received a pulse oximetry screening for CCHDs. For births attended by midwives who received pulse oximeters from MDHHS, 50.5% had pulse oximetry screening results reported, compared with 12.7% among births attended by midwives without a loaned pulse oximeter. Of the 78 total midwives, 18% (n = 14) reported pulse oximetry screening results on more than half of the births they attended. Of the 14 midwives who received a pulse oximeter from MDHHS, 50.0% (n = 7) reported screening results for more than half of all births they attended. Discussion: Our findings indicate that CCHD screening rates are low among midwife‐attended out‐of‐hospital birth community. Screening rates were higher among midwives who received a pulse oximeter from MDHHS, but fewer than half of the attended births had a reported pulse oximetry screening. Further discussions with the midwife‐attended out‐of‐hospital birth community to better understand screening barriers may be beneficial.